التقييم الإنشائي للأبنية البيتونية المسلحة المتصدعة - كيخيا عبد الحميد (Latakia University Journal -Engineering Sciences Series, 2016)
تطورت في الأونة الأخيرة نظريات وأساليب التقييم الفني والإنشائي للأبنية المتصدعة لأسباب مختلفة (الكوارث الطبيعية ، الحروب ، القدم .....الخ) ، وذلك بسبب الحاجة الماسة لعملية التقييم الصحيحة ، والوقوف على حقيقة الوضع الإنشائي والوظيفي للبناء ، واتخاذ القرار المناسب . يتضمن البحث توضيح أهمية عملية التقيم الإنشائي للأبنية ، وأسس ومعايير تصنيف الأبنية المتصدعة حسب وضعها الإنشائي والفني ، وسبل اتخاذ القرار المناسب لكيفية التعامل مع الأبنية المتصدعة . تعتبر عملية التقييم الفني والإنشائي للأبنية البيتونية المسلحة ، عملية فريدة من نوعها لا تتكرر ولها خصوصية لارتباطها بمجموعة كبيرة من المتحولات (بنية وطبيعة مادة البيتون ، الجملة الإنشائية ، شدة وطبيعة التصدعات والانهيارات ....الخ ) لذلك فإن عملية التقييم تقوم على مجموعة من القياسات والاختبارات والمشاهدات ، لذلك فإن الخبرة الشخصية للمهنس تلعب دورا مهما في عملية التقييم . يتضمن البحث إعداد منهجية علمية لعملية التقييم ، وتصميم برنامج حاسوبي للقيام بعملية التقييم الفني والإنشائي للأبنية المتصدعة ، وذلك للحد من الدور الشخصي والمزاجي للمهندس في عملية التقييم ، كما يتضمن تطبيق على حالات واقعية . Recently, the methods and theories of the structural and technicalevaluation for cracked buildings have been developed because of different reasons (Natural disasters, wars, the oldness… etc.) That was due to urgent need for right evaluation process, understand the structural and function status of the building and make the right decision. The research includes the clarification of the importance of building structural evaluation in addition to the basis and criteria of cracked buildings classification regarding their structural and technical status. The structural and technical evaluation for concrete building is considered as non-repetitive unique process, which has its particularity due to its link with large group of indicators ( concrete natural and structure- structural system - the natural and intensity of failures and cracks …etc.) Therefore, the evaluation process based on groups of measurements, tests and views. The personal experience of the engineer has an important role at evaluation process. The research includes the preparation of scientific methodology to evolution process and designing structural and technical evaluation software to evaluate cracked buildings and limit the personal and mood role of the engineer during evaluation process. In addition to that, the software will include applications from the real situations.